IMPROVEMENT METHODS OF DIAGNOSING LEAKAGE FROM THE PIPELINE ON THE BASIS OF RESEARCH DISTURBANCES PROPAGATION PROCESS - Грудз, Володимир Ярославович; Грузд (молодший), Володимир Ярославович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Questions of improving the diagnosis of small accidental leaks from the pipeline, based on the analysis of non-stationary processes induced perturbation of occurrence of leakage. The estimation of the impact of the profile of the pipeline on the accuracy of the coordinates of the leak. We analyze the dependence of the velocity of small perturbations in the flow of gas from the nature of the process and its parameters. The influence of the parameters of the gas and its moisture content to change the velocity of sound waves in the gas stream. in a heterogeneous mixture with water drops. The conclusions of the feasibility and necessity of considering the speed of sound depending on the profile in diagnosing problems.